PENDEKATAN ALGORITMA CROSS ENTROPY-GENETIC ALGORITHM UNTUK MENURUNKAN MAKESPAN PADA PENJADWALAN FLOW SHOP - Widodo, Dian Setiya; Santoso, Purnomo Budi; Siswanto, Eko (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2014)
Â In the flow shop scheduling each job will go through every machine in the same order. The goal of this research is to complete a series of jobs in order to obtain the optimal makespanÂ for stick skewers rounding machine. It is become necessities because the company has no planning and scheduling, while the demand exceeds the capacity Thus, optimize the scheduling is needed to be done. One way to optimize the scheduling is to minimize makespan. Based on the results of the research Cross Entropy Algorithm-Genetic Algorithm (CEGA) can provide the optimal solution. This is evident by a comparison technique that enumeration techniques obtained similar results with makespan 1982 seconds, but when compared to the company, CEGA method is better with makespan efficiency of 12.18%. The use of CEGA with the MATLAB has more advantages that simplify and speed in performing the calculations to can optimal solution.Â